Impact of cyberloafing and physical exercise on performance: an experimental research - Santos, Ana Sara Teixeira (2017)
All organizations want to be successful and part of their success is directly connected with their employees’ performance. Many factors influence employees’ performance thus it is important for an organization to identify them. This study aims to analyze the effect that cyberloafing and physical exercise have on individual’s performance. Built upon an innovative perspective, a laboratory experimental research was developed where a total of 124 participants perform two different tasks, a cognitive task and a motor task, and their performance was evaluated after a break doing cyberloafing activities and physical exercise. Results revealed that cyberloafing has a negative effect in both cognitive and motor performance while physical exercise has a positive effect in both cognitive and motor performance. Conscientiousness and engagement were also found to be moderators of these relationships with regard to cognitive performance, showing a huge positive effect along with physical exercise. Theoretical and practical implications as well as limitations of the study and areas for future research were also explored.